Satellite-based hyperspectral imaging and cartographic visualization of bark beetle forest damage for the City of Čabar - Kranjčić, Nikola (Array, 2018)
After enormous amount of ice rain during 2014 huge damage was done in forests in Croatia, especially in the city of Čabar area. Damage of forests is reflected in wide spread of bark beetle. Bark beetle damaged forest have different spectral range from healthy forest. Copernicus satellite land monitoring imagery enables distinguishing healthy from unhealthy forest. In this paper, the width of bark beetle infection spread in forests in the city of Čabar area using satellite images and semi-automatic classification will be determined.